Implementasi Test Kepribadian untuk Meningkatkan Rasa Percaya Diri - Ainun Pangestu Putri Munif; Aisyah Zulfa Aidah; Camala Irza Nurul Khoiriyah; Fatwa Khoerunisa; Kasma Wati; Ria Indah; Yulia Apriyanti (Concept: Journal of Social Humanities and Education, 2025)
In the process of finding their identity, the younger generation really needs knowledge about themselves. This involves understanding the strengths one has and how these strengths can be optimized and utilized for one’s own growth. Insecurity or insecurity is a psychological condition that is commonly experienced by many people. Feelings of insecurity can cause various negative effects, such as anxiety, depression, and low self-confidence. This article discusses ways to reduce feelings of insecurity by deepening personality knowledge. By deepening personality knowledge, a person can learn to know themselves better, increase self-confidence, and build healthy relationships with other people. This can help reduce feelings of insecurity and improve quality of life.